2005
DOI: 10.1055/s-2005-837552
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Knife Surgery is Effective in Normalising Plasma Insulin-Like Growth Factor I in Patients with Acromegaly

Abstract: We have shown that pituitary gamma-knife surgery is effective in lowering serum IGF-I levels. At the end of the follow-up period, 48 % of our cohort had normal age-adjusted IGF-I levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…This suggests that CK SRS is an effective adjuvant for acromegalic patients with persistent, active disease following surgery or medical therapy. The rate of biochemical remission or control achieved is similar to that seen with other forms of SRS [31,32,[34][35][36], and as recently well summarized by Sheehan et al [39]. The mean time to serum IGF-1 normalization was 12 months.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This suggests that CK SRS is an effective adjuvant for acromegalic patients with persistent, active disease following surgery or medical therapy. The rate of biochemical remission or control achieved is similar to that seen with other forms of SRS [31,32,[34][35][36], and as recently well summarized by Sheehan et al [39]. The mean time to serum IGF-1 normalization was 12 months.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, 14 (17%) patients developed at least one new anterior pituitary deficiency, but the incidence of other side effects was rare [32]. Further studies using SRS (typically Gamma Knife) on smaller numbers of subjects have shown control rates ranging from 23 to 90% [33][34][35][36][37]. In addition, Landolt et al [11] showed that 16 patients treated with adjuvant Gamma Knife radiosurgery achieved rates of biochemical remission comparable to those in 50 patients who received fractionated RT.…”
Section: Discussionmentioning
confidence: 57%
“…1,7,8,10,16,19,22,23,[25][26][27][28]30,33,34,[37][38][39][40][41][42]45,[47][48][49]51 The mean reported patient age was 45.2 ± 3.78 years. The overall mean duration of reported follow-up was 48.5 ± 25.8 months, and the overall median duration of reported follow-up was a similar 46.6 ± 20.4 months.…”
Section: Results Of Systematic Analysismentioning
confidence: 99%
“…Of these 951 patients, 472 (49.6%) achieved biochemical remission following SRS based on study-dependent endocrine criteria. 1,7,8,10,16,19,22,23,[25][26][27]30,[37][38][39][40][41][42]45,[47][48][49]51 When considering only those studies that used GH < 2.5 ng/ml or oral glucose tolerance test, GH < 1 ng/ml and normal IGF-I compared with age-and sexmatched controls as their criteria for biochemical remission, 44.5% of patients achieved disease control following SRS without medication. Utilizing a more stringent criteria of age-matched IGF-I normalization levels in series of 10 patients or more, our analysis revealed a similar 52.5% disease control rate in 506 patients with acromegaly treated using SRS.…”
Section: Analysis Of Endocrine Parameters and Srsmentioning
confidence: 99%
“…In recent years, conventional RT has been progressively replaced by stereotactic RT, the major reasons being better target selectivity with lower incidence of cerebral vascular disease and secondary neoplasia [15] and a shorter latency period to achieve hormonal control [16][17][18].…”
Section: Discussionmentioning
confidence: 99%